Experimental investigation of seismic behavior of confined cavity walls retrofitted with reactive powder concrete overlays. (29th April 2019) - Yang, Kejia; Dai, Tao; Li, Wei; Huang, Bin
Abstract: Brick cavity wall structures are widely distributed in southeastern China; however, their integrity and seismic behavior are extremely poor. To solve this problem, a new technique is proposed to enhance the seismic behavior of brick cavity walls using steel fiber reactive powder concrete (SFRPC) overlays. Two unreinforced cavity walls and four cavity walls strengthened with SFRPC overlays (applied over the entire wall surface) were tested under cyclic loading. In this study, the damage and failure modes of the specimens were analyzed in terms of the load displacement curves; furthermore, a comparative investigation was performed considering the load capacity, ductility, stiffness degradation, and energy dissipation capacity to demonstrate the merits of brick cavity walls strengthened with SFRPC overlays. The effect of strengthening using different thicknesses of reinforcement was investigated. In addition, damage analyses of the walls were performed based on the modified Park–Ang damage assessment model.